Use of Rh Immune Globulin in First-Trimester Abortion and Miscarriage. Issue 1 (30th January 2023) - Gilmore, Emma; Sonalkar, Sarita; Schreiber, Courtney A.
Abstract : Limited evidence supports offering Rh immune globulin to Rh-negative women for first-trimester bleeding events, such as miscarriage or abortion, and this practice may need reconsideration.